Politics of dialogue : non-consensual democracy and critical community - Koczanowicz, Leszek (Edinburgh University Press, 2015)
Contemporary democracy is in crisis. People believe less and less in a system of democratic institutions that can cope with today's social problems. Leszek Koczanowicz sheds new light on this problem, using the ideas of M.M. Bakhtin and others to show that dialogue in democracy can transcend both antagonistic and consensual perspectives. Koczanowicz provides an overview of the history of the dialogue/antagonism opposition as it is embedded in modern political theory, and the concept of dialogue in contemporary political theory. He goes on to demonstrate that Bakhtin's theory of dialogism can introduce a new quality into political theory, allowing us to overcome the liberalism/communitarianism debate. To conclude, he introduces a concept of 'critical community' - a dialogical, self-reflective community critical of its own tradition - to show that collective identities can be constructed in critical dialogue with the tradition and values of community.